2018
DOI: 10.3747/co.25.4379
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Perspectives: Update on Inhibition of ALK-Positive Tumours in Advanced Non-Small-Cell Lung Cancer

Abstract: BackgroundInhibition of the anaplastic lymphoma kinase (alk) oncogenic driver in advanced non-small-cell lung carcinoma (nsclc) improves survival. In 2015, Canadian thoracic oncology specialists published a consensus guideline about the identification and treatment of ALK-positive patients, recommending use of the alk inhibitor crizotinib in the first line. New scientific literature warrants a consensus update.MethodsClinical trials of alk inhibitor were reviewed to assess benefits, risks, and implications rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
(107 reference statements)
0
15
0
Order By: Relevance
“…In our study, the initial ALK inhibitor was likely a first-generation ALK inhibitor given the time frame of the study. Treatment guidelines currently recommend the use of multiple ALK inhibitors [ 21 , 24 ]. Our findings support sequencing through ALK therapies before proceeding to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the initial ALK inhibitor was likely a first-generation ALK inhibitor given the time frame of the study. Treatment guidelines currently recommend the use of multiple ALK inhibitors [ 21 , 24 ]. Our findings support sequencing through ALK therapies before proceeding to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The WBRT-30-SCLC needs to be validated in a separate cohort of patients in the future because advances in systemic therapies, especially the development immuno-therapies that can cross the blood-brain-barrier will have an impact on the survival of patients with brain metastases from lung cancer. Promising results were reported for immune checkpoint inhibitors or alk inhibitors in patients with brain metastases from non-small cell lung cancer [23,24,25,26]. Moreover, a phase 2 study of maintenance pembrolizumab in 45 patients with extensive disease SCLC, of whom 22% had treated brain metastases, suggested that a subset of these patients could benefit from this treatment [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the model can produce estimates that approximate recent reports of ALK patient survival, but base-case estimates may be more indicative of general aNSCLC patient survival as opposed to survival of patients at academic centers or in clinical trials. As new effective treatment approaches [42] are more broadly adopted, iTEN estimates of survival are likely to increase.…”
Section: Discussionmentioning
confidence: 99%